2018
DOI: 10.3389/fenvs.2018.00018
|View full text |Cite
|
Sign up to set email alerts
|

Belowground Carbon Dynamics in Tropical Perennial C4 Grass Agroecosystems

Abstract: Effective soil management is critical to achieving climate change mitigation in plant-based renewable energy systems, yet limitations exist in our understanding of dynamic belowground responses to the cultivation of energy crops. To better understand the belowground dynamics following cultivation of a grassland in a high-yielding tropical perennial C4 grass in a zero-tillage production system, changes in soil carbon (C) pools were quantified, modeled, and projected and the chemical composition of the aggregate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1
1

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 54 publications
1
18
0
Order By: Relevance
“…The lower temperature was the mean annual temperature for multiple field sites under study at the same time, and the higher temperature is ∼2°C higher than the mean annual temperature of the site and corresponds with the projected global temperature increase range scenarios for Hawaii (Giambelluca et al, 2013; IPCC, 2014). The details of the incubation may be found in Crow et al (2018), which reported the raw cumulative CO 2 efflux curves as a proxy for the amount of active C, readily accessible to microbes. Briefly, 10 g of soil (the dry weight equivalent) was brought to field capacity and placed in an incubation jar fitted with a septa and equilibrated for 48 h at the designated temperature within two C‐controlled environment chambers (Model 6021‐1, Caron Products & Services).…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…The lower temperature was the mean annual temperature for multiple field sites under study at the same time, and the higher temperature is ∼2°C higher than the mean annual temperature of the site and corresponds with the projected global temperature increase range scenarios for Hawaii (Giambelluca et al, 2013; IPCC, 2014). The details of the incubation may be found in Crow et al (2018), which reported the raw cumulative CO 2 efflux curves as a proxy for the amount of active C, readily accessible to microbes. Briefly, 10 g of soil (the dry weight equivalent) was brought to field capacity and placed in an incubation jar fitted with a septa and equilibrated for 48 h at the designated temperature within two C‐controlled environment chambers (Model 6021‐1, Caron Products & Services).…”
Section: Methodsmentioning
confidence: 99%
“…Finally, mineral‐associated C was isolated within the dense fraction. The details may be found in Crow et al (2018), which reported the C pool size of density fractions as representations of unprotected organic debris (free light fraction), aggregate‐protected organic matter (occluded light fraction), and mineral‐associated organic C (dense fraction). Briefly, 20 g of soil (dry weight equivalent) was fractionated in a 1.8‐g mL −1 solution of sodium polytungstate, and the free light fraction was isolated by gently shaking and removing the floating material by suction.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations